Linguistic minorities in the South African context : the case of Tshivenda - Luvhengo, Nkhangweleni (Rhodes University, Faculty of Humanities, School of Languages, 2013)
After many years of the oppressive apartheid government, the new democratic era came into being in 1994. Lot of policy changes came into being, including language policy. This new language policy of the post-apartheid era recognises eleven official languages which include the nine indigenous African languages which were previously recognised as regional languages in the different homelands. The present study investigates the progress of Tshivenda in terms of status and development since it was accorded the official status in South Africa. Literature investigating the status of Tshivenda is generally sparse. This study investigates the status of Tshivenda in South Africa to explore how minority languages which are also recognised as official languages are treated. In most multilingual countries, there are issues which affect the development of minority languages, but the South African situation is interesting in that some of the minority languages are recognised as official languages. This study is a comparative in nature. Firstly, the study compares the level of corpus planning and development in Tshivenda and other indigenous South African languages. Secondly, it compares how people use Tshivenda in a rural area of Lukalo Village where the language is not under pressure from other languages and in Cosmo City, an urban area in Gauteng where Tshivenda speakers come into contact with speakers of more dominant languages such as isiZulu and Sesotho. Language use in different domains like, media, education, government and the home is considered in order to establish how people use languages and the factors which influence their linguistic behaviours. The study also establishes the perceptions and attitudes of the speakers of Tshivenda as a minority and those of the speakers of other languages towards Tshivenda's role in the different domains such as education and the media. This study was influenced by previous research (Alexander 1989, Webb 2002) which found out that during the apartheid period Tshivenda speakers used to disguise their identity by adopting dominant languages like isiZulu and Sesotho in Johannesburg. Accordingly, the present research wanted to establish how the language policy change in the democratic era has impacted on the confidence of Tshivenda speakers regarding themselves and their language. This study establishes that although Tshivenda is now an official language in post-apartheid South Africa, it still has features of underdevelopment and marginalization that are typically of unofficial minority languages. Translation, lexicographic and terminological work in this language still lags behind that of other indigenous South African languages and there is still a shortage of school textbooks and adult literature in this language. As a result, using the language in education, the media and other controlling domains is still quite challenging, although positive developments such as the teaching of the language at university level can be noted. The Tshivenda speakers generally have a positive attitude towards their language and seem prepared to learn and use it confidently as long its functional value is enhanced, which is currently not happening. As a result, some Tshivenda speakers still regard English as a more worthwhile language to learn at the expense of their language
Keywords: Indigenous African languages; Apartheid; Tshivenda; Minority languages; Development; Status; Multilingualism; Sesotho; isiZulu; Perceptions; Linguistic minorities -- Research -- South Africa; Venda language -- Research -- South Africa; Language policy -- Research -- South Africa; Multilingualism -- Research -- South Africa; Linguistic rights -- Research -- South Africa; Language and languages -- Political aspects